Insider trading: preventions and its enforcement in Malaysia / Yusni Abd Kahar - Abd Kahar, Yusni (1993)
Insider trading is not an alien phrase to those who are involved in the business world. Its existence has been known since America suffered its worst stock market crash in 1929 but is beginning to capture the general public attention when the SEC of the United States brought the case of Ivan Boesky to court and then followed by Stephen Chang, Micheal Milken and many more. In Malaysia, eventhough there is no case is being brought to court yet, but there are regulations provided by the Malaysian Government to prevent insider trading practices. The regulations are provided in various Acts and the government also has appointed the ROC to be responsible in enforcing these regulations.